While stairing up: perceiving shades of academic motivation of high school first-generation learners and desired academic outcomes - Susmita Sengupta; Sanat Kumar Guchhait (Discover Education)
Abstract What motivates a first-generation learner to go to school? The question haunts a social scientist when exploring dimensions of academic motivation of the first-generation Learners in rural and remote context. Learners from the low Socio-Economic Status are ‘at risk’ of academic motivation, cohere with specific psychological behaviours leading to academic failure. Gathering quantitative and qualitative data, the study opts to capture dimensions of motivational constructs of first-generation Learners. The study adopts explanatory sequential research design that entails triangulating quantitative statistical results with qualitative findings to validate the outcome of the study. The student participants were 1554 selected through stratified random sampling using gender, social affiliation and grade as criteria for getting hierarchy. The findings include steady decline of academic motivation of Learners in the secondary level of school education under the lens of socio-economic context, home environment and school and neighborhood quality perceiving academic, and psychological hardships as the outcome.